Climate‐induced warming imposes a threat to north European spring ecosystems. (December 2015) - Jyväsjärvi, Jussi; Marttila, Hannu; Rossi, Pekka M.; Ala‐Aho, Pertti; Olofsson, Bo; Nisell, Jakob; Backman, Birgitta; Ilmonen, Jari; Virtanen, Risto; Paasivirta, Lauri; Britschgi, Ritva; Kløve, Bjørn; et al.
Abstract: Interest in climate change effects on groundwater has increased dramatically during the last decade. The mechanisms of climate‐related groundwater depletion have been thoroughly reviewed, but the influence of global warming on groundwater‐dependent ecosystems (GDEs) remains poorly known. Here we report long‐term water temperature trends in 66 northern European cold‐water springs. A vast majority of the springs (82%) exhibited a significant increase in water temperature during 1968–2012. Mean spring water temperatures were closely related to regional air temperature and global radiative forcing of the corresponding year. Based on three alternative climate scenarios representing low (RCP2.6), intermediate (RCP6) and high‐emission scenarios (RCP8.5), we estimate that increase in mean spring water temperature in the region is likely to range from 0.67 °C (RCP2.6) to 5.94 °C (RCP8.5) by 2086. According to the worst‐case scenario, water temperature of these originally cold‐water ecosystems (regional mean in the late 1970s: 4.7 °C) may exceed 12 °C by the end of this century. We used bryophyte and macroinvertebrate species data from Finnish springs and spring‐fed streams to assess ecological impacts of the predicted warming. An increase in spring water temperature by several degrees will likely have substantial biodiversity impacts, causing regional extinction of native, cold‐stenothermal spring specialists, whereas species diversity of headwater generalists is likely to increase. Even a slight (by 1 °C) increase in water temperature may eliminate endemic spring species, thus altering bryophyte and macroinvertebrate assemblages of spring‐fed streams. Climate change‐induced warming of northern regions may thus alter species composition of the spring biota and cause regional homogenization of biodiversity in headwater ecosystems.